The assessment of Spondyloarthritis International Society Health Index (ASAS HI) in patients with spondyloarthritis - a single centre experience - Maida Skokić; Almira Ćosićkić; Adin Alić (Medicinski glasnik, 2024)
Aim The Assessment of Spondyloarthritis International Society Health Index (ASAS HI) Croatian version was used to assess health and functioning of patients with spondyloarthritis (SpA) covering aspects of physical, emotional and social functioning. Methods A cross sectional study was conducted at the Clinic for Internal Diseases Tuzla from January to June 2021. Inclusion criteria: fulfilled the ASAS diagnostic criteria for SpA. Exclusion criteria: failure to fulfil the diagnostic criteria, acute infection, the use of antibiotics in the past month, malignancy, associated disorders, psychiatric disorders, pregnancy, patient’s refusal to take part in the study. The Disease Activity Score with C reactive protein values (ASDAS-CRP) was assessed. Results Eighty three patients (43 male and 40 female) fulfilled the study criteria with median age of 54 years. The median value of ASDAS-CRP was 2.15, since ASAS HI had the median of 8 (interquartile range; IQR: 2-13) points. Patients with inactivity and with low disease activity had the ASAS HI median of 2 (IQR: 0-6) and 5 (IQR: 1-9) points, respectively. Significantly higher values of ASAS HI were found in patients with moderate and high disease activity, males (13.5 and 16) and females (13 and 14), respectively. The correlation between ASDAS-CRP and ASAS HI, (r=0.62; p<0.0009) was positive, statistically significant. However, the significant correlation between disease duration and ASAS HI values was not found (r=0.11; p=0.28). Conclusion The ASAS HI, Croatian version, is valid and reliable disease specific questionnaire for the assessment of health status in patients with SpA in the Bosnian speaking area.
Keywords: arthritis rheumatoid; joints; quality of life